Production of natural folates by lactic acid bacteria starter cultures isolated from artisanal Argentinean yogurts - Laiño, Jonathan Emiliano (2012)
Folate is a B-group vitamin that cannot be synthesized by humans and must be obtained exogenously. Although some species of lactic acid bacteria (LAB) can produce folates, little is known on the production of this vitamin by yogurt starter cultures. Lactobacillus (L.) bulgaricus and Streptococcus (St.) thermophilus strains were isolated from artisanal Argentinean yogurts and were grown in folate-free culture medium (FACM) and nonfat milk after which intra- and extra cellular folate production were evaluated. From the initial 92 isolated LAB strains, 4 L. bulgaricus and 32 St. thermophilus were able to grow in absence of folate. L. bulgaricus CRL 863 and St. thermophilus CRL 415 and CRL 803 produced the highest extracellular folate levels (from 22.3 to 135 ìg/L) in FACM. In nonfat milk, these strains were able to increase the initial folate concentrations almost 190%. This is the first report where native strains of L. bulgaricus were shown to produce natural folate. The LAB strains identified in this study could be used in developing novel fermented products bio-enriched in natural folates that could in turn be used as an alternative to fortification with the controversial synthetic chemical folic acid.